Toward deceiving the intrusion attacks in containerized cloud environment using virtual private cloud‐based moving target defense. (30th November 2022) - Hyder, Muhammad Faraz; Ahmed, Waqas; Ahmed, Maaz
Summary: The container‐based cloud has its distinct security challenges. In this article, moving target defense (MTD) is used to increase the cost and effort of the attacker to exploit resources and follow an attack path to compromise the critical resources in a container‐based cloud. The existing MTD mechanisms for cloud have not focused on intruder prevention inside containerized environment. The proposed solution is one of its kind that utilizes resource movement inside and across the virtual private network in the cloud to deceive intruders. The framework continuously changes the target/container to increase confusion about the routing path, so attackers cannot follow the simple attack path. This obscure cloud architecture increases the delay in attack and gives system/network administrators significant time to use Intrusion Detection mechanisms for countering the attack. The proposed scheme is implemented on the Google Cloud Platform (GCP) by using an extensive network of nodes hosting the stateful pods that are created and destroyed periodically. The experimental analysis confirmed that the proposed scheme substantially increased the attack path length and added obscurity at a low computation cost. However, as per experiments, implementing the proposed scheme in GCP slightly increases the dollar cost.